2020
DOI: 10.1080/15299732.2020.1787296
|View full text |Cite
|
Sign up to set email alerts
|

From Individual To Social Trauma: Sources Of Everyday Trauma In Italy, The US And UK During The Covid-19 Pandemic

Abstract: The heterogeneity of COVID-19 experience and response for each individual is irrefutable; nevertheless, similarities can be observed between countries with respect to people's psychological responses. The main aim of this Commentary is to provide a cultural perspective of the sources of trauma, at the individual and social level, in three different countries: Italy, US and UK. The evidence from previous outbreaks, such as SARS, H1N1 flu, Ebola, and the ongoing Italian, the US, and the UK experience of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
125
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 20 publications
3
125
0
2
Order By: Relevance
“…As rapidly pointed out ( Fiorillo and Gorwood, 2020 ; Jakovljevi et al, 2020 ), the COVID-19 global pandemic has affected—and is still affecting—not only physical health but also individual, family, and collective mental health. In line with recent studies ( Horesh and Brown, 2020 ; Masiero et al, 2020 ), the COVID-19 pandemic should be classified as a critical event with a potential traumatic nature, which may be overwhelming and could lead to complex emotional responses that can negatively affect individuals and collective psychological systems.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…As rapidly pointed out ( Fiorillo and Gorwood, 2020 ; Jakovljevi et al, 2020 ), the COVID-19 global pandemic has affected—and is still affecting—not only physical health but also individual, family, and collective mental health. In line with recent studies ( Horesh and Brown, 2020 ; Masiero et al, 2020 ), the COVID-19 pandemic should be classified as a critical event with a potential traumatic nature, which may be overwhelming and could lead to complex emotional responses that can negatively affect individuals and collective psychological systems.…”
Section: Introductionmentioning
confidence: 59%
“…As stated above, in addition to being a public physical health emergency, the COVID-19 pandemic also implies a global mental health emergency that may have a potential traumatic nature and provoke complex emotional responses that could negatively affect individual and collective mental health ( Jakovljevi et al, 2020 ; Masiero et al, 2020 ). Therefore, this global pandemic constantly requires researchers and professionals to monitor and assess the current mental health situation, in order to plan and develop efficiency-driven strategies aimed to reduce its negative psychological impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to adapt to the complex environment, HCWs use heuristics that become inevitable ( Mazzocco and Cherubini, 2010 ), and lead to mistakes. On top of that, preliminary studies on trauma during the COVID-19 pandemic ( Li et al, 2020 ) suggested that HCWs may experience vicarious traumatization and emotional dissociation from what they are seeing and experiencing ( Masiero et al, 2020 ): this may lead to PTSD if not timely managed. PTSD may have tremendous consequences and should be monitored not only in the patients’ population ( Arnaboldi et al, 2014 ) but also in the HCWs’ one.…”
Section: Discussionmentioning
confidence: 99%
“…Even after the COVID-19 pandemic is over, its repercussions likely will linger for years. Medical researchers confirmed that the psychological consequences of COVID-19 resemble the symptoms of post-traumatic stress disorder (Masiero et al 2020;Tang et al 2020), which means that prioritizing the wellness of students, even at the cost of less efficiency of instruction, may be a desirable modification that educators should address, at least during the times of social isolation and mental stress that accompany the pandemic. Meanwhile, instructors should keep in mind that video feedback is not panacea for any learning scenario.…”
mentioning
confidence: 99%